Repurposing AZD-5991 for inhibiting growth and biofilm formation of Staphylococcus aureus by disrupting the cell membrane and targeting FabI - Yuanyuan Tang; Han Deng; Zhichao Xu; Zhijian Yu; Yong Xiang; Zewen Wen; Shiqing Han; Zhong Chen; Tieying Hou (BMC Microbiology)
Abstract Staphylococcus aureus infections have emerged as a global public health threat. Two key factors—drug resistance and biofilm formation—substantially impair the efficacy of the antimicrobial treatment for S. aureus infections using conventional antibiotics. Consequently, discovering novel antimicrobial agents with potent antibacterial and antibiofilm activity has become a hotspot in recent years. Herein, the research first reported the remarkable inhibitory activity of AZD-5991, a selective Mcl-1 inhibitor, against S. aureus. The MIC50 and MIC90 values of AZD-5991 against S. aureus were 12.5 µM, and significant growth inhibition was observed at a subinhibitory concentration of 1/2 × MIC. Additionally, AZD-5991 exhibited bactericidal activity and a robust capacity for inhibiting S. aureus biofilm formation, with minimal cytotoxicity toward host cell lines. Membrane permeability assays revealed that AZD-5991 compromised S. aureus cell membrane integrity, while bacterial phospholipid components were found to neutralize the antibacterial activity of AZD-5991. Moreover, whole-genome sequencing and proteomic analysis were also applied to gain insights into the possible impact of AZD-5991 on the fatty metabolism of S. aureus. Furthermore, the antibacterial activity of AZD-5991 was remarkably declined by exogenous fatty acids linoleic acid (C18:2Δ9,12) and arachidonic acid (C20:4Δ5,8,11,14). Lastly, the biolayer interferometry assay supported the direct interaction of AZD-5991 with FabI, a key protein essential for bacterial growth and fatty acid metabolism. Conclusively, this study demonstrates that AZD-5991 inhibits S. aureus planktonic growth and biofilm formation by disrupting cell membrane integrity and targeting FabI. These findings position AZD-5991 as a promising novel antibiotic candidate for treating S. aureus infections resistant to traditional clinical antibiotics. Graphical Abstract